Tritium distributions on W-coated divertor tiles used in the third JET ITER-like wall campaign. (January 2019) - Hatano, Y.; Lee, S.E.; Likonen, J.; Koivuranta, S.; Hara, M.; Masuzaki, S.; Asakura, N.; Isobe, K.; Hayashi, T.; Ikonen, J.; Widdowson, A.; ,
Highlights: Tritium distributions on tungsten-coated divertor tiles used in the third ITER-like wall (ILW) campaign (2015–2016) of the Joint European Torus (JET) were examined by means of an imaging plate technique and β-ray induced x-ray spectrometry. The obtained tritium distributions were compared with those after the first (2011–2012) and the second (2013–2014) ILW campaigns. Tritium concentrations in the deposition layers of Be and other impurities formed in the third ILW campaign were significantly low in comparison with the first and second ILW campaigns. Abstract: Tritium (T) distributions on tungsten (W)-coated plasma-facing tiles used in the third ITER-like wall campaign (2015–2016) of the Joint European Torus (JET) were examined by means of an imaging plate technique and β-ray induced x-ray spectrometry, and they were compared with the distributions after the second (2013–2014) campaign. Strong enrichment of T in beryllium (Be) deposition layers was observed after the second campaign. In contrast, T distributions after the third campaign was more uniform though Be deposition layers were visually recognized. The one of the possible explanations is enhanced desorption of T from Be deposition layers due to higher tile temperatures caused by higher energy input in the third campaign.